The Midland Economy and Society, 1314-1348: Insights from Changes in the Landscape. (2nd January 2017) - Dyer, Christopher
Abstract: The economic and social trends in the period between the famine of 1315–17 and the plague epidemic of 1348–50 are difficult to understand. This article uses changes in the landscape to broaden the scope of the inquiry into the economic trajectory of those years. Worcester Cathedral Priory had expanded the size and number of tenant holdings by allocating pieces of demesne land just before the famine. In 1336–40 tenants were granted land taken from the waste or from the demesne, in many cases explicitly to build new houses The new holdings can be traced on the ground, and their landscape context identified. The attempt to grow rent income to protect the monastery from the effects of recession was short lived, though the new settlements did not immediately fail. Similar ventures can be found on other estates. The well-documented organisation of new settlements has implications for the role of medieval lords in landscape planning.